The trouble with post-Blackness - Baker, Houston A., Jr., 1943-; Simmons, Merinda, 1981- (Columbia University Press, 2015)
"Post-Blackness salutes Black individuals and their achievements while rejecting affiliation with any larger Black community. It disavows allegiance to Black intellectual and cultural traditions. Its stance depends on the premise that the current racial order has broken with the past. This collection of commissioned essays begins a long overdue discussion about changes in the racial order in the age of Obama. It interrogates and challenges the emergence of post-Black ideology from a variety of perspectives. It examines how we pay attention to the ways in which Blackness has been patterned and imagined in America. Making use of a wide scope of topics that rally around central questions introduced by the notion of post-Blackness, the volume gives general readers and students an introduction to what it means to be 'Black' in the twenty-first century"--Provided by publisher